Excess BAFF May Impact HIV-1-Specific Antibodies and May Promote Polyclonal Responses Including Those from First-Line Marginal Zone B-Cell Populations - Kim Doyon-Laliberté; Matheus Aranguren; Josiane Chagnon-Choquet; Laurie-Anne Batraville; Olina Dagher; Jonathan Richard; Matteo Paniconi; Jean-Pierre Routy; Cécile Tremblay; Marie-Claude Quintal; Nathalie Brassard; Daniel E. Kaufmann; et al. (Current Issues in Molecular Biology, 2023)
We have previously shown that blood levels of B-cell Activating Factor (BAFF) rise relatively to disease progression status in the context of HIV-1 infection. Excess BAFF was concomitant with hyperglobulinemia and the deregulation of blood B-cell populations, notably with increased frequencies of a population sharing characteristics of transitional immature and marginal zone (MZ) B-cells, which we defined as marginal zone precursor-like” (MZp). In HIV-uninfected individuals, MZp present a B-cell regulatory (Breg) profile and function, which are lost in classic-progressors. Moreover, RNASeq analyses of blood MZp from classic-progressors depict a hyperactive state and signs of exhaustion, as well as an interferon signature similar to that observed in autoimmune disorders such as Systemic Lupus Erythematosus (SLE) and Sjögren Syndrome (SS), in which excess BAFF and deregulated MZ populations have also been documented. Based on the above, we hypothesize that excess BAFF may preclude the generation of HIV-1-specific IgG responses and drive polyclonal responses, including those from MZ populations, endowed with polyreactivity/autoreactivity. As such, we show that the quantity of HIV-1-specific IgG varies with disease progression status. In vitro, excess BAFF promotes polyclonal IgM and IgG responses, including those from MZp. RNASeq analyses reveal that blood MZp from classic-progressors are prone to Ig production and preferentially make usage of IGHV genes associated with some HIV broadly neutralizing antibodies (bNAbs), but also with autoantibodies, and whose impact in the battle against HIV-1 has yet to be determined.